Vertical transmission of Trypanosoma evansi in experimentally infected rats - Campigotto G.* (2017)
© 2017 Elsevier Inc.Many reproductive problems has been described in male and female animals infected by Trypanosoma evansi. Thus, the aim of this study was to evaluate the occurrence of vertical (Experiment I) and venereal (Experiment II) transmission of T. evansi in rats experimentally infected. In the experiment I, eight female Wistar rats were used: three animals as negative controls, and five rats were infected by T. evansi on day ten of gestation. Out of these eight females, half puppies were used for molecular analysis (polymerase chain reaction - PCR) for T. evansi. Two infected females showed delivery problems, such as stillbirth, and fetal death that also led to female death. Three female rats infected had normal delivery of stunted offspring at term that died 2 days after birth. Rats from the control group had normal delivery of healthy offspring. T. evansi PCR was positive for 80% (12/15) of pups in the infected group. For the experiment II, five male rats were infected by T. evansi, and monitored by blood smears to check the parasitemia level. When the male rats showed parasitemia between 2 and 5 parasites per field, they were individually housed with one female adult rat. After approximately 21 days, the females delivered their offspring. Blood sample was collected from the females for blood smears and T. evansi PCR tests, which revealed negative results. Therefore, we were able to prove the occurrence of transplacental transmission of T. evansi and its negative effect on female rats and their offspring.